Analisa Karakteristik Pompa Dan Laju Temperatur Fluida Pada Alat Pilot Plant Biodiesel: Pilot Plant Biodesel - Suryadi Suryadi; Muhammad Sayuthi; Muhammad Habibi (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
Today's technological growth is very rapid, companies continue to develop in technological innovation in their products. At the same time, it is necessary to increase adequate energy such as electric power, chemical power, and renewable alternative fuels to replace diesel oil, namely Biodiesel. As of January 2020, the government has implemented a fuel mixture for the transportation sector containing 30% biodiesel in diesel oil. There are many types of biodiesel processing technologies, including non-catalyst technology. This technology only requires raw materials in the form of oil and methanol, without using a catalyst. The use of methanol in the form of superheated vapor in a non-catalyzed response requires equipment that can replace liquid methanol into superheated methanol vapor. The conversion of methanol to superheated methanol in this research was carried out using a methanol preheater based on a design from previous research using the ChemCAD application. namely heating methanol indirectly through a heating fluid in the form of Mobiltherm 605 thermal oil. With mobiltherm hot at a temperature of 50ºC, the pump performance results are obtained with Capacity (Q) 0.0003 m^3/s, Head (H) 0.019 m, Power hydraulic (N_h) 119 watts, and efficiency (η) 95.2%. The greater the value of the density of the fluid, the greater the power used. In the case of Mobiltherm, which has a different fluid viscosity from water, the hydraulic power and efficiency obtained are also high. The mobiltherm 605 heat transfer rate is 35% through the double pipe annulus and the methanol temperature rate through the double pipe inner pipe